True broad ligament fibroid mimicking ovarian mass in a postmenopausal woman - Singh, Lata; Gupta, Taru; Kumari, Snigdha; Gupta, Sangeeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Fibroids are benign smooth muscle tumors. Large fibroids are known to arise from the uterus, but occasionally from the broad ligament. Here, we report a case of true broad ligament fibroid which is rare and difficult to diagnose in a 57 year old postmenopausal women with a large mass of 24 weeks size gravid uterus. Patient presented with pain lower abdomen and mass in abdomen with no other co-morbidity. This broad ligament fibroid was mimicking as ovarian tumor on ultrasonography and MRI as left ovary was not visualised separately, thus leading to diagnostic dilemma of ovarian malignancy. Mass resection with total abdominal hysterectomy and bilateral salpingo-oopherectomy was performed. No local or distant metastasis observed, and Histopathology showed true broad ligament fibroid of left side weighing 3.57 kilograms.